Dual mission of startups: defining and situating the concept - Sady, Monika; Buła, Piotr (Contemporary organisation and management. Challenges and trends, 2020)
The main business goal of a startup is usually fast development and ultimately generating satisfactory profits. However, there are startups whose main purpose is not only to maximize financial profits, but to have a positive social impact. This noble business idea has many representatives: inspirational startups operating in the field of eco-innovation, social innovation, social change and social entrepreneurship. This article explores the ideation and practice of the concept of startups with dual mission. Literature review situates the idea within a broader context of socially responsible business practices, social innovation, social entrepreneurship and dual mission. The article is also an attempt to show what legal forms can be used for startups with dual mission in Poland.